High-temperature-resistant porous aramid fiber lithium battery diaphragm and preparation method thereof
By using aramid parapolymerization stock solution of components such as PVDF, PEG and 2,5-furandiformyl chloride in the lithium battery separator, a porous aramid lithium battery separator is formed, which solves the problem of poor thermal stability of the lithium battery separator and improves the safety and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202510556802.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-08-01
AI Technical Summary
The existing lithium battery separators have poor thermal stability and low safety performance, which can easily cause thermal runaway from the battery.
Polyvinylidene fluoride (PVDF), polyethylene glycol (PEG) and 2,5-furandiformyl chloride are used to enhance the aramid parapolymerization stock solution, and the porous aramid lithium battery separator is formed by coating to improve the thermal stability and bonding strength of the separator.
In high temperature environments, the thermal shrinkage rate of the separator is reduced, avoiding short circuits caused by contact with positive and negative electrode materials, enhancing battery safety, and ensuring smooth transmission of lithium ions, improving battery safety performance.
Smart Images

Figure CN120413987A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and particularly relates to a high-temperature resistant porous aramid lithium battery separator and a preparation method thereof. Background Art
[0002] With the acceleration of the urbanization process and the increasing awareness of environmental protection, consumers' demands for new energy vehicles with low emissions, energy conservation and environmental protection, high-end 3C electronics, large-scale energy storage, etc. are growing continuously. The hot demand side market of new energy vehicles has driven the development of related industries, especially the demand for separators.
[0003] The separator is a key material to ensure the safety of the lithium battery system and improve the electrochemical performance. Traditional separators are mostly polyolefin separators, which have poor thermal stability and are prone to cause thermal runaway of the battery and trigger safety accidents. As a kind of special engineering material, aramid-coated separators have performance advantages such as good heat resistance, good electrolyte wettability, and good oxidation resistance, and are one of the ultimate solutions for lithium battery separators. Different from inorganic ceramic-coated separators, aramid-coated separators have a double-layer microporous structure. The bottom layer is a microporous membrane of polyolefin, and the porosity is generally 30% - 50%. The commonly used polyolefin material is ultra-high molecular weight polypropylene. Its main function is that when the battery temperature approaches or exceeds the melting point of polyolefin, the micropores in the polyolefin will quickly close, thereby playing a role in protecting the battery; and the coating layer is a relatively dense aramid network microporous membrane, which can still ensure no membrane breakage in a short time after the substrate fails, greatly reducing the probability of battery thermal runaway. Due to extremely high technical barriers and strict intellectual property protection, at present, only Sumitomo Chemical and Teijin in Japan have achieved the commercialization of aramid-coated separators and have been applied to Tesla Model S new energy vehicles and Apple mobile phones respectively. Domestic separator manufacturers purchase aramid fibers externally. Due to the poor solubility of aramid fibers, the consistency of the slurry is poor, it is difficult to achieve pore structure regulation, and the technical maturity is relatively low, and there is no large-scale production.
[0004] Therefore, developing aramid-coated separator technology and realizing the domestic substitution of high-end lithium battery separator materials is of great significance for comprehensively improving the safety performance and electrical performance of domestic power batteries and promoting the high-quality development of the terminal new energy vehicle industry. Summary of the Invention
[0005] To solve the problems of poor thermal stability and low safety performance of lithium battery separators in the prior art, the present invention provides a high-temperature resistant porous aramid lithium battery separator and its preparation method. During the preparation of the lithium battery separator, polyvinylidene fluoride (PVDF) effectively enhances the binding force between the para-aramid pre-polymerization stock solution and the polypropylene film, and polyethylene glycol (PEG) significantly improves the air permeability of the surface of the aramid stock solution and the polypropylene film. Notably, the third monomer 2,5-furandicarbonyl chloride plays an irreplaceable and unique role in the entire material system. In the practical application of lithium battery separators, insufficient thermal stability has always been a key factor threatening battery safety. The deterioration of separator performance under high-temperature environments may cause serious problems such as battery short circuits. However, due to its special molecular structure, 2,5-furandicarbonyl chloride can act synergistically with other components after being added, greatly improving the thermal stability of the lithium battery separator. Through experimental testing, the dimensional stability of the separator under high-temperature environments is significantly improved after adding this monomer, effectively suppressing the shrinkage, deformation, etc. of the separator caused by temperature changes, and thus significantly enhancing the safety performance of the lithium battery separator. It provides a strong guarantee for the safe and efficient operation of lithium batteries.
[0006] The present invention first provides a high-temperature resistant porous aramid lithium battery separator, which uses a polypropylene film as the base film, and at least one side of the base film is coated with a para-aramid pre-polymerization stock solution.
[0007] In the raw materials of the para-aramid polymerization stock solution, the mass percentage of polyvinylidene fluoride is 3 - 5%, the mass percentage of polyethylene glycol is 10 - 20%, and the molar ratio of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride is 1:(0.5 - 0.9):(0.05 - 0.45). The solvent system of the polymerization stock solution is a mixed system of N-methylpyrrolidone (NMP)-CaCl2 solution, and its ratio is 100 ml NMP:8 g CaCl2; the total molar amount of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride corresponding to every 100 ml of NMP is 1.85 - 1.95 mol.
[0008] Furthermore, in the raw materials of the para-aramid polymerization stock solution, the mass percentage of polyvinylidene fluoride is 3 - 4%, the mass percentage of polyethylene glycol is 13 - 15%, and the molar ratio of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride is 1:(0.75 - 0.9):(0.1 - 0.2).
[0009] In the technical solution of the present application, it is preferably to coat on one side of the base film, because coating on both sides will reduce the air permeability of the separator; the thickness of the polypropylene film in the porous aramid lithium battery separator is 12 - 14 µm, and the coating thickness of the para-aramid polymerization stock solution is 19 - 22 µm.
[0010] Further, in the raw materials of the para-aramid polymerization stock solution, the mass percentage of polyvinylidene fluoride is 3%, the mass percentage of polyethylene glycol is 15%, and the molar ratio of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride is 1:0.75:0.2.
[0011] The separator provided by the present invention has a minimum thermal shrinkage rate that can be controlled within 5% at a high temperature of 180°C, and basically does not shrink or deform, thus greatly avoiding the short-circuit phenomenon caused by the contact of the positive and negative electrode materials in a high-temperature environment; through the bond strength test, the bond strength between the separator and the electrode can reach more than 5 N / cm, ensuring the stability of the separator in the battery; the air permeability of the separator can reach 300 - 400 s / 100 mL, ensuring the smooth transmission of lithium ions inside the battery; the thermal decomposition temperature of the separator can be increased to more than 350°C, greatly enhancing the safety of the battery in a high-temperature environment.
[0012] In addition, the inventor further provides a preparation method for the above-mentioned high-temperature-resistant porous aramid lithium battery separator, and the specific steps are as follows: (1) After heating the N-methylpyrrolidone (NMP)-CaCl2 solution mixture system in an oil bath to a certain temperature, polyethylene glycol (PEG) and polyvinylidene fluoride (PVDF) are added in sequence, stirred and dispersed evenly, then cooled to a certain temperature in an ice-water bath, p-phenylenediamine is added, and the reaction is allowed to completely dissolve. Then, 2,5-furandicarbonyl chloride and terephthaloyl chloride are added to start the polycondensation polymerization reaction, which lasts for 10 - 20 minutes to control the molecular weight of the polymer and make its viscosity slowly increase, with the viscosity range being 0.9 - 3.2 mpa·s. Finally, the para-aramid prepolymerization stock solution is prepared by polymerization; The N-methylpyrrolidone (NMP)-CaCl2 solution mixture system is prepared by dissolving CaCl2 in the organic solvent NMP in an oxygen-free and water-free environment, with a ratio of 100 ml NMP:8 g CaCl2; the oil bath is heated to 80°C; after polyethylene glycol and polyvinylidene fluoride are stirred and dispersed evenly, the temperature is cooled to 0 ± 10°C in an ice-water bath; (2) The para-aramid polymerization stock solution prepared in step (1) is directly coated on one side of the polypropylene film by a coater, with a coating thickness of 19 - 22 µm, and dried at 60 - 80°C for 30 - 60 min; (3) The polypropylene film coated with the para-aramid stock solution is placed in N-methylpyrrolidone / H2O and left to stand for phase transformation, causing the homogeneous polymer solution to undergo phase separation until the polypropylene film is completely bonded to the coating solution, and finally solidifying into a film; (4) The phase-transformed aramid / polypropylene film is placed in a vacuum drying oven for drying to remove the moisture in the composite separator, and a para-aramid / polypropylene composite separator is obtained, which is the high-temperature-resistant porous aramid lithium battery separator.
[0013] The above reaction is mainly a polymerization reaction for preparing para-aramid nanofibers. As the reaction proceeds, the viscosity of the system will gradually increase. At the same time, the added polyvinylidene fluoride (PVDF) also plays a role in this regard. The finally obtained polymerization stock solution has a certain viscosity and air permeability, and also has good thermal stability. Among them, PVDF can improve the bonding force between the para-aramid polymerization stock solution and the polypropylene film. After being dispersed in an organic solvent and mixed with the aramid slurry, the stock solution can better adhere to the polypropylene film during coating and is not easy to fall off; PEG is used as a pore-forming agent to improve the air permeability of the coated separator and helps to form a porous structure during the subsequent phase transition process. Para-phenylenediamine is added after PEG and PVDF are stirred evenly and cooled to 0±10°C. As one of the raw materials for the polymerization reaction, it undergoes a polycondensation reaction with the acyl chloride monomer added subsequently to form an aramid polymer; 2,5-furandicarbonyl chloride and terephthaloyl chloride are added after para-phenylenediamine is completely dissolved. The two undergo a polycondensation reaction with para-phenylenediamine to form aramid. Because 2,5-furandicarbonyl chloride contains a rigid group, it can improve the thermal stability and safety performance of the lithium battery separator; terephthaloyl chloride participates in the polymerization reaction and jointly constructs the molecular structure of aramid with other monomers, which can affect the performance of the polymer.
[0014] Compared with the prior art, the feature of this application lies more in the use of 2,5-furandicarbonyl chloride, which is specifically manifested in: 1. As a polymerization monomer, 2,5-furandicarbonyl chloride undergoes a polycondensation reaction with diamine monomers commonly used in aramid polymerization (such as para-phenylenediamine). Its two acyl chloride groups (-COCl) can react with the amino groups (-NH2) of the diamine monomer through a reaction mechanism of removing hydrogen chloride (HCl) to form amide bonds (-CONH-), thereby introducing a furan structure into the molecular chain of aramid, realizing the growth of the molecular chain and the formation of the polymer.
[0015] 2. Affect the molecular chain structure and properties, introduce a furan ring: The furan ring in 2,5-furandicarbonyl chloride is a five-membered heterocyclic ring with a rigid and conjugated structure. Introducing it into the aramid molecular chain can increase the rigidity and regularity of the molecular chain, enhance the interaction between molecular chains, and help improve the heat resistance, mechanical properties, and chemical stability of aramid.
[0016] 3. Improve the polymerization reaction conditions. 2,5-furandicarbonyl chloride has a relatively high reaction activity and a fast reaction rate with diamine monomers, and can achieve efficient polymerization under relatively mild reaction conditions. This helps to shorten the polymerization reaction time, reduce the reaction energy consumption, and improve the production efficiency. At the same time, the fast reaction rate can reduce the occurrence of side reactions, improve the controllability of the molecular weight and molecular weight distribution of the polymer, and thus obtain aramid products with stable properties.
[0017] In the step (1), the mass percentage of polyvinylidene fluoride in the mixed system is 3-5%, and the mass percentage of polyethylene glycol is 10-20%; the molar ratio of p-phenylenediamine: terephthaloyl chloride: 2,5-furandicarbonyl chloride is 1: (0.5-0.9): (0.05-0.45). After adding terephthaloyl chloride and 2,5-furandicarbonyl chloride, the polymerization reaction time is controlled within 10-20 minutes to control the molecular weight range of the polymer within 500-22000, and the corresponding viscosity range is 0.9-3.2 mpa·s. If the viscosity is too low, the polymer molecular chain is short, and the obtained coating strength is insufficient; if the viscosity is too high, the fluidity of the original solution is poor, and it is difficult for the para-aramid original solution to form a film.
[0018] Furthermore, to provide a suitable solvent environment for the reaction, ensure that the reactants can be fully dissolved and dispersed, and facilitate the smooth progress of the polymerization reaction, the dosage of the above NMP-CaCl2 salt solution is preferably 100 ml; the mass percentage of polyvinylidene fluoride in the mixed system is preferably 3%, and the mass percentage of polyethylene glycol (PEG) is preferably 15%. The molar ratio of p-phenylenediamine: terephthaloyl chloride: 2,5-furandicarbonyl chloride is preferably 1:0.75:0.2, and the total molar amount of the three is 1.95 moI.
[0019] Mass percentage of polyvinylidene fluoride 3%: While ensuring the improvement of the bonding force between the para-aramid polymerization stock solution and the polypropylene film, it will not affect other properties such as air permeability due to excessive content, and can be well dispersed in the reaction system; mass percentage of polyethylene glycol 15%: It can effectively improve the air permeability of the separator, form a suitable pore structure, and will not damage the overall structure and strength of the separator due to excessive content; molar ratio of p-phenylenediamine: terephthaloyl chloride: 2,5 - furandicarbonyl chloride 1:0.75:0.2: At this ratio, the formed aramid polymer has good comprehensive properties, balancing thermal stability, mechanical properties, etc. Excessive or too little 2,5-furandicarbonyl chloride will affect thermal stability, and improper proportion of terephthaloyl chloride will affect the molecular structure and properties of the polymer.
[0020] In the step (2), the thickness of the polypropylene-based film is 12-14 µm, and further preferably, the thickness is 12 µm; the coating thickness is 19-22 µm, and further preferably 19 µm; vacuum drying is adopted, and the drying temperature is further preferably 70 °C, and the drying time is further preferably 30 min.
[0021] In the step (3), N-methylpyrrolidone (NMP) is used as a phase transition solvent, and the volume ratio of NMP to H2O is 3-7:7-3; more preferably 3:7, and the phase transition time is 6-18 h, and further preferably 12 h. By observing that the coating solution on the surface of the coated separator does not fall off after phase transition, it indicates that there is bonding force, which is the end point of phase transition.
[0022] In step (4), the aramid / polypropylene separator after phase transition is dried in a vacuum drying oven, and the temperature is selected to be 60-80°C. If the temperature is lower than 60°C, it is not easy to dry out the moisture inside; if it is higher than 80°C, the solvent NMP is likely to volatilize. Therefore, the drying temperature is further preferably 70°C, the drying time is 6-12h, and further preferably 6h; the vacuum degree is 0.09MPa.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: Adding polyethylene glycol (PEG), polyvinylidene fluoride (PVDF), and 2,5-furandicarbonyl chloride to the polymerization stock solution can effectively increase the proportion of organic fillers (N-methylpyrrolidone, polyethylene glycol, polyvinylidene fluoride, and 2,5-furandicarbonyl chloride) in the aramid coating solution. The interaction of these raw materials significantly enhances the thermal stability of the separator prepared from this aramid coating solution. After testing, the thermal shrinkage rate of the optimized separator can be controlled within 5% at a high temperature of 180°C, and basically no shrinkage deformation occurs, thus greatly avoiding the short-circuit phenomenon caused by the contact of the positive and negative electrode materials in a high-temperature environment. After polyvinylidene fluoride (PVDF) is dispersed in an organic solvent and stirred evenly with the aramid slurry, the bonding performance of the aramid coating solution can be effectively improved. After the bonding strength test, the bonding strength between the separator prepared with this coating solution and the electrode can reach more than 5N / cm, ensuring the stability of the separator in the battery. Polyethylene glycol (PEG) is used as a pore-forming agent, effectively improving the air permeability of the coated separator. After detection, the air permeability of the separator can reach 300-400s / 100mL, ensuring the smooth transmission of lithium ions inside the battery. The third monomer 2,5-furandicarbonyl chloride contains a rigid group, and its addition further improves the thermal stability of the lithium battery separator, thereby improving the safety performance of the lithium battery separator. In terms of thermal stability, in addition to the above thermal shrinkage rate index, the thermal decomposition temperature of this separator can be increased to above 350°C, greatly enhancing the safety of the battery in a high-temperature environment. Description of the Drawings
[0024] Figure 1 It is the SEM diagram of the structure of the aramid polymerization-coated polypropylene composite separator prepared in Example 5 of the present invention; Figure 2 It is the TG curve of the aramid polymerization stock solution prepared in Example 5 of the present invention containing the monomer 2,5-furandicarbonyl chloride (black line) and Comparative Example 1 without adding 2,5-furandicarbonyl chloride (red line). Detailed Embodiments
[0025] The technical solutions of the present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solutions of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.
[0026] Example 1 A method for preparing a high-temperature resistant porous aramid lithium battery separator, the specific steps are as follows: (1) Add 8 g of CaCl2 to 100 ml of NMP. In this salt solution mixture system, sequentially add 2.4 g of polyethylene glycol (PEG) and 4 g of polyvinylidene fluoride (PVDF) under an 80°C oil bath heating, stir and disperse evenly. Then cool it down to (0±10°C) with an ice-water bath, add 2.163 g of p-phenylenediamine, continue to react for 20 minutes to completely dissolve it. Then add 1.737 g of 2,5-furandicarbonyl chloride and 2.030 g of terephthaloyl chloride, and carry out a polymerization reaction for 20 minutes to slowly increase its viscosity. Finally, obtain an aramid para-position polymerization stock solution with a viscosity of 1.2 mPa·s. This stock solution has high air permeability and high thermal stability.
[0027] (2) Set the coating thickness of the aramid para-position polymerization stock solution prepared in step (1) to 19 µm on a coater, and directly coat it on one side of a 14-µm-thick polypropylene base film. Then adjust the temperature to rise to 70°C and heat the composite separator for 20 min.
[0028] (3) Prepare an NMP / H2O aqueous solvent with a volume ratio of NMP:H2O of 3:7. Place the polypropylene film coated with the aramid para-position stock solution in the NMP / H2O solvent for phase inversion for 6 h; make the homogeneous polymer solution undergo phase separation until the polypropylene film is completely bonded to the coating solution, and finally solidify into a film.
[0029] (4) Place the phase-inverted aramid / polypropylene film in a vacuum drying oven and dry it for 6 h. Adjust the temperature of the drying oven to 70°C and the vacuum degree to 0.09 MPa. Finally, obtain a para-aramid / polypropylene composite separator.
[0030] Example 2 A method for preparing a high-temperature resistant porous aramid lithium battery separator, the specific steps are as follows: (1) Add 8 g of CaCl2 to 100 ml of NMP. In this salt solution mixture system, sequentially add 3.2 g of polyethylene glycol (PEG) and 6 g of polyvinylidene fluoride (PVDF) under an 80°C oil bath heating, stir and disperse evenly. Then cool it down to (0±10°C) with an ice-water bath, add 2.163 g of p-phenylenediamine, continue to react for 20 minutes to completely dissolve it. Then add 1.3541 g of 2,5-furandicarbonyl chloride and 2.436 g of terephthaloyl chloride, and carry out a polymerization reaction for 20 minutes to slowly increase its viscosity. Finally, obtain an aramid para-position polymerization stock solution with a viscosity of 1.38 mPa·s. This stock solution has high air permeability and high thermal stability.
[0031] (2) Set the coating thickness of the para-aramid polymerization stock solution prepared in step (1) to 20 µm on a coater, and directly coat it on one side of a polypropylene base film with a thickness of 14 µm. Then adjust the temperature to rise to 70 °C and heat the composite separator for 20 min.
[0032] (3) Prepare an NMP / H2O aqueous solvent with a volume ratio of NMP:H2O of 50%:50%, and place the polypropylene film coated with the para-aramid stock solution in the NMP / H2O solvent for phase inversion for 6 h.
[0033] (4) Place the phase-inverted aramid / polypropylene film in a vacuum drying oven and dry it for 6 h. Adjust the temperature of the drying oven to 70 °C and the vacuum degree to 0.09 MPa to finally obtain a para-aramid / polypropylene composite separator.
[0034] Example 3 A preparation method of a heat-resistant porous aramid lithium battery separator, the specific steps are as follows: (1) Add 8 g of CaCl2 to 100 ml of NMP. In this salt solution mixing system, sequentially add 2.4 g of polyethylene glycol (PEG) and 4 g of polyvinylidene fluoride (PVDF) under an 80 °C oil bath heating, stir and disperse evenly. Then cool it down to (0 ± 10 °C) with an ice-water bath, add 2.163 g of p-phenylenediamine, and continue to react for 20 minutes to completely dissolve it. Then add 0.965 g of 2,5-furandicarbonyl chloride and 2.842 g of terephthaloyl chloride, and carry out a polymerization reaction for 20 minutes to slowly increase its viscosity, and finally obtain a para-aramid polymerization stock solution with a viscosity of 1.89 mPa·s.
[0035] (2) Set the coating thickness of the para-aramid polymerization stock solution prepared in step (1) to 19 µm on a coater, and directly coat it on one side of a polypropylene base film with a thickness of 14 µm. Then adjust the temperature to rise to 70 °C and heat the composite separator for 20 min.
[0036] (3) Prepare an NMP / H2O aqueous solvent with a volume ratio of NMP:H2O of 70%:30%, and place the polypropylene film coated with the para-aramid stock solution in the NMP / H2O solvent for phase inversion for 6 h.
[0037] (4) Place the phase-inverted aramid / polypropylene film in a vacuum drying oven and dry it for 6 h. Adjust the temperature of the drying oven to 70 °C and the vacuum degree to 0.09 MPa to finally obtain a para-aramid / polypropylene composite separator.
[0038] Example 4 A preparation method of a heat-resistant porous aramid lithium battery separator, the specific steps are as follows: (1) Add 8 g of CaCl₂ to 100 ml of NMP. In this salt solution mixture system, successively add 2.4 g of polyethylene glycol (PEG) and 4 g of polyvinylidene fluoride (PVDF) under an 80 °C oil bath heating, stir and disperse evenly. Then cool it down to (0 ± 10 °C) using an ice-water bath, add 2.163 g of p-phenylenediamine, continue the reaction for 20 minutes to completely dissolve it. Then add 0.579 g of 2,5-furandicarbonyl chloride and 3.248 g of terephthaloyl chloride, and carry out a polymerization reaction for 20 minutes to slowly increase its viscosity. Finally, obtain an aramid para-position polymerization stock solution with a viscosity of 2.38 mPa·s.
[0039] (2) Set the coating thickness of the aramid para-position polymerization stock solution prepared in step (1) to 19 µm on a coater, and directly coat it on one side of a 14-µm-thick polypropylene base film. Then adjust the temperature to rise to 70 °C and heat the composite diaphragm for 20 min.
[0040] (3) Prepare an NMP / H₂O aqueous solvent with an NMP:H₂O volume ratio of 30%:70%, and place the polypropylene film coated with the aramid para-position stock solution in the NMP / H₂O solvent for phase inversion for 6 h.
[0041] (4) Place the phase-inverted aramid / polypropylene film in a vacuum drying oven and dry it for 6 h. Adjust the temperature of the drying oven to 70 °C and the vacuum degree to 0.09 MPa. Finally, obtain a para-aramid / polypropylene composite diaphragm.
[0042] Example 5 A preparation method of a heat-resistant porous aramid lithium battery diaphragm, the specific steps are as follows: (1) Add 8 g of CaCl₂ to 100 ml of NMP. In this salt solution mixture system, successively add 2.4 g of polyethylene glycol (PEG) and 4 g of polyvinylidene fluoride (PVDF) under an 80 °C oil bath heating, stir and disperse evenly. Then cool it down to (0 ± 10 °C) using an ice-water bath, add 2.163 g of p-phenylenediamine, continue the reaction for 20 minutes to completely dissolve it. Then add 0.193 g of 2,5-furandicarbonyl chloride and 3.654 g of terephthaloyl chloride, and carry out a polymerization reaction for 20 minutes to slowly increase its viscosity. Finally, obtain an aramid para-position polymerization stock solution with a viscosity of 2.75 mPa·s.
[0043] (2) Set the coating thickness of the aramid para-position polymerization stock solution prepared in step (1) to 19 µm on a coater, and directly coat it on one side of a 14-µm-thick polypropylene base film. Then adjust the temperature to rise to 70 °C and heat the composite diaphragm for 20 min.
[0044] (3) Prepare an NMP / H₂O aqueous solvent with an NMP:H₂O volume ratio of 30%:70%, and place the polypropylene film coated with the aramid para-position stock solution in the NMP / H₂O solvent for phase inversion for 6 h.
[0045] (4) Place the aramid / polypropylene film after phase transition in a vacuum drying oven and dry it for 6 h. Adjust the temperature of the drying oven to 80 °C and the vacuum degree to 0.09 MPa to finally obtain a para-aramid / polypropylene composite separator.
[0046] Comparative Example 1 A method for preparing an aramid lithium battery separator, the specific steps are as follows: (1) Add 8 g of CaCl2 to 100 ml of NMP. In this salt solution mixing system, sequentially add 2.4 g of polyethylene glycol (PEG) and 4 g of polyvinylidene fluoride (PVDF) under an 80 °C oil bath heating, stir and disperse evenly, then cool it to (0 ± 10 °C) with an ice-water bath, add 2.163 g of p-phenylenediamine, continue to react for 20 minutes to completely dissolve it, then add 3.857 g of terephthaloyl chloride, and carry out a polymerization reaction for 20 minutes to slowly increase its viscosity, finally obtaining an aramid para-position polymerization stock solution with a viscosity of 3.12 mPa·s.
[0047] (2) Set the coating thickness of the aramid para-position polymerization stock solution prepared in step (1) on the coater to 19 µm, directly coat it on one side of a 14-µm-thick polypropylene base film, then adjust the temperature to rise to 70 °C and heat the composite separator for 20 min.
[0048] (3) Prepare an NMP / H2O aqueous solvent with a volume ratio of NMP:H2O of 30%:70%, and place the polypropylene film coated with the aramid para-position stock solution in the NMP / H2O solvent for phase transition for 6 h.
[0049] (4) Place the aramid / polypropylene film after phase transition in a vacuum drying oven and dry it for 6 h. Adjust the temperature of the drying oven to 60 °C and the vacuum degree to 0.09 MPa to finally obtain a para-aramid / polypropylene composite separator.
[0050] Comparative Example 2 A method for preparing an aramid lithium battery separator, the specific steps are as follows: (1) Add 8 g of CaCl2 to 100 ml of NMP. In this salt solution mixing system, stir and disperse evenly, then cool it to (0 ± 10 °C) with an ice-water bath, add 2.163 g of p-phenylenediamine, continue to react for 20 minutes to completely dissolve it, then add 0.193 g of 2,5-furandicarbonyl chloride and 3.654 g of terephthaloyl chloride, and carry out a polymerization reaction for 20 minutes to slowly increase its viscosity, finally obtaining an aramid para-position polymerization stock solution with a viscosity of 0.98 mPa·s.
[0051] (2) Set the coating thickness of the aramid para-position polymerization stock solution prepared in step (1) on the coater to 19 µm, directly coat it on one side of a 14-µm-thick polypropylene base film, then adjust the temperature to rise to 70 °C and heat the composite separator for 20 min.
[0052] (3) Prepare an NMP / H2O aqueous solvent with an NMP:H2O volume ratio of 30%:70%, and place the polypropylene film coated with the para-aramid spinning dope in the NMP / H2O solvent for phase inversion for 6 h.
[0053] (4) Place the phase-inverted aramid / polypropylene film in a vacuum drying oven and dry it for 6 h. Adjust the temperature of the drying oven to 70 °C and the vacuum degree to 0.09 MPa to finally obtain a para-aramid / polypropylene composite separator.
[0054] Experimental Example Carry out relevant performance tests on the para-aramid polymerization spinning dope / polypropylene composite separators prepared in the above-mentioned examples and comparative examples in accordance with GB / T 36363-2018 "Polyolefin Separators for Lithium-Ion Batteries", and the results are shown in Table 1 below: Table 1 Note: The thickness is the final thickness of the para-aramid coating.
[0055] Table 1 shows the performance parameters of the para-aramid lithium-ion battery separators obtained in Examples 1-5 and Comparative Examples 1-2. Comparative Examples 1-2 are two reaction systems without the third monomer 2,5-furandicarbonyl chloride and without polyethylene glycol (PEG) and polyvinylidene fluoride (PVDF) respectively. Examples 1-5 are the addition of different ratios of 2,5-furandicarbonyl chloride and terephthaloyl chloride and different mass fractions of polyethylene glycol (PEG) and polyvinylidene fluoride (PVDF). The results show that the gas permeability of the lithium-ion battery separator is greatly affected by the addition of polyethylene glycol (PEG), and the gas permeability has been significantly improved. In addition, the addition of the third monomer 2,5-furandicarbonyl chloride also greatly improves the heat resistance of the lithium-ion battery separator and reduces the thermal shrinkage rate of the separator.
[0056] The separator provided by the present invention has a minimum thermal shrinkage rate of less than 5% at a high temperature of 180 °C, and basically does not shrink and deform, thus greatly avoiding the short-circuit phenomenon caused by the contact of the positive and negative electrode materials in a high-temperature environment; the bonding strength between the separator and the electrode can reach more than 5 N / cm through the bonding strength test, ensuring the stability of the separator in the battery; at the same time, the gas permeability of the separator is ensured, thus ensuring the smooth transmission of lithium ions inside the battery; the thermal decomposition temperature of the separator can be increased to more than 350 °C, greatly enhancing the safety of the battery in a high-temperature environment.
[0057] Figure 1 SEM diagram of the structure of the aramid polymerization-coated polypropylene composite separator prepared for Example 5; through Figure 1The scanning electron microscope can, on the one hand, reveal the network structure of the aramid polymerization stock solution, and on the other hand, it also confirms that the added polyethylene glycol (PEG) has a pore-forming effect, showing a rich porous structure.
[0058] Figure 2 TG curves of the aramid polymerization stock solutions prepared in Example 5 and Comparative Example 1 are shown. During the preparation of the aramid polymerization stock solution in Example 5, 2,5-furandicarbonyl chloride was added, while in Comparative Example 1, 2,5-furandicarbonyl chloride was not added. Figure 2 It can be seen that the weight loss rate of the polymer in Example 5 is very low and relatively stable below 500 °C. When the temperature is higher than 500 °C, a very obvious weight loss occurs, and the weight loss rate is about 48%. The weight loss rate of the para-aramid polymerization stock solution prepared in Comparative Example 1 without doping 2,5-furandicarbonyl chloride is higher than that of the para-aramid polymerization stock solution doped with 2,5-furandicarbonyl chloride in Example 5, indicating that the para-aramid polymerization stock solution added with 2,5-furandicarbonyl chloride has excellent heat resistance below 500 °C.
[0059] In addition, the inventors also detected other properties of the separator. Since materials such as aramid and PVDF have stable chemical properties, the separator has enhanced tolerance to various chemical substances in the electrolyte. After being immersed in the electrolyte for a long time, the size and structure of the separator do not change significantly, and no impurities are generated due to chemical reactions with the electrolyte, which will not affect the battery performance, thus extending the battery life. At the same time, polyethylene glycol (PEG) as a pore-forming agent optimizes the pore structure of the separator, making the transmission path of lithium ions in the separator smoother, improving the ionic conductivity of the separator, accelerating the migration rate of lithium ions during the charge and discharge process of the battery, and enhancing the charge and discharge efficiency of the battery.
[0060] In summary, by adding the binder polyvinylidene fluoride PVDF and polyethylene glycol (PEG) to the aramid polymerization stock solution, compared with traditional separators, the present invention can greatly improve the bonding force between the para-aramid polymerization stock solution and the base film, making it not easy to fall off. Through the experimental results of the examples and comparative examples, polyethylene glycol (PEG) as a pore-forming agent optimizes the pore structure of the separator, which can well improve the air permeability performance of the coated separator. At the same time, it improves the ionic conductivity of the separator, accelerates the migration rate of lithium ions during the charge and discharge process of the battery, and enhances the charge and discharge efficiency of the battery. The addition of the third monomer 2,5-furandicarbonyl chloride improves the thermal stability of the coated separator, enhances the safety of the battery, and effectively reduces the risk of battery thermal runaway.
[0061] The above-described embodiments are only descriptions of the preferred embodiments of the present invention, and do not limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations and improvements made by those of ordinary skill in the art to the technical solutions of the present invention should fall within the protection scope determined by the claims of the present invention.
Claims
1. A porous aramid lithium battery separator with high temperature resistance, using a polypropylene film as the base film, characterized in that, At least one side of the base film is coated with the para-aramid prepolymer stock solution. In the para-aramid polymerization stock solution, the mass percentage of polyvinylidene fluoride is 3 - 5%, the mass percentage of polyethylene glycol is 10 - 20%, and the molar ratio of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride is 1:(0.5 - 0.9):(0.05 - 0.45).
2. The high-temperature resistant porous aramid lithium battery separator according to claim 1, wherein Among the raw materials of the para-aramid polymerization stock solution, the mass percentage of polyvinylidene fluoride is 3 - 4%, the mass percentage of polyethylene glycol is 13 - 15%, the molar ratio of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride is 1:(0.75 - 0.9):(0.1 - 0.2), the solvent system of the polymerization stock solution is a mixed system of N-methylpyrrolidone - CaCl2 solution, and its ratio is 100 ml NMP:8 g CaCl2; the total molar amount of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride corresponding to every 100 ml NMP is 1.85 - 1.95 moI.
3. The high-temperature resistant porous aramid lithium battery separator according to claim 1 or 2, characterized in that In the porous aramid lithium battery separator, the thickness of the polypropylene film is 12 - 14 µm, and the coating thickness of the para-aramid polymerization stock solution is 19 - 22 µm.
4. The preparation method of the high-temperature resistant porous aramid lithium battery separator material according to claim 1, characterized in that, The specific steps are as follows: (1) After heating the mixed system of N-methylpyrrolidone - CaCl2 solution to a certain temperature in an oil bath, successively add polyethylene glycol and polyvinylidene fluoride, stir and disperse evenly, then cool to a certain temperature with an ice-water bath, add p-phenylenediamine, react to completely dissolve it, then add 2,5-furandicarbonyl chloride and terephthaloyl chloride, start the polycondensation polymerization reaction, continue for 10 - 20 minutes, and finally polymerize to obtain the para-aramid prepolymer stock solution; Among them, the mass percentage of polyvinylidene fluoride in the mixed system is 3 - 5%, the mass percentage of polyethylene glycol is 10 - 20%, the molar ratio of p-phenylenediamine:terephthaloyl chloride:2,5-furandicarbonyl chloride is 1:(0.5 - 0.9):(0.05 - 0.45); the solvent system of the polymerization stock solution is a mixed system of N-methylpyrrolidone - CaCl2 solution, and its ratio is 100 ml NMP:8 g CaCl2; the total molar amount of p-phenylenediamine, terephthaloyl chloride, and 2,5-furandicarbonyl chloride corresponding to every 100 ml NMP is 1.95 moI; (2) Directly coat the para-aramid polymerization stock solution prepared in step (1) on one side of the polypropylene film with a coating thickness of 19 - 22 µm, and dry it at 60 - 80 °C for 30 - 60 min; (3) Place the polypropylene film coated with the para-aramid stock solution in N-methylpyrrolidone / H2O and let it stand for phase transition to cause phase separation of the homogeneous polymer solution until the polypropylene film is completely bonded to the coating solution, and finally cure it into a film; (4) Place the phase-transitioned aramid / polypropylene film in a vacuum drying oven to dry and remove the moisture in the composite separator to obtain a para-aramid / polypropylene composite separator, which is a high-temperature resistant porous aramid lithium battery separator.
5. The preparation method of the high-temperature resistant porous aramid lithium battery separator material according to claim 1, characterized in that, In the step (1), the N-methylpyrrolidone-CaCl₂ solution mixture system is prepared by dissolving CaCl₂ in the organic solvent NMP under an anaerobic and anhydrous environment. The ratio is 100 ml of NMP: 8 g of CaCl₂. It is heated in an oil bath to 80 °C. After polyethylene glycol and polyvinylidene fluoride are stirred and dispersed evenly, the temperature is lowered to 0 ± 10 °C in an ice bath.
6. The preparation method of the high-temperature resistant porous aramid lithium battery separator material according to claim 4 or 5, characterized in that, In the mixture system of the step (1), the mass percentage of polyvinylidene fluoride is 3%, the mass percentage of polyethylene glycol is 15%, and the molar ratio of p-phenylenediamine: terephthaloyl chloride: 2,5-furandicarbonyl chloride is 1: 0.75: 0.
2.
7. The preparation method of the high-temperature resistant porous aramid lithium battery separator material according to claim 4, characterized in that, In the step (2), the thickness of the polypropylene-based membrane is 12 - 14 µm, and the thickness of the coating is 19 - 22 µm.
8. The preparation method of the high-temperature resistant porous aramid lithium battery separator material according to claim 4, characterized in that, In the step (2), the drying temperature is 70 °C and the drying time is 30 min.
9. The preparation method of the high-temperature resistant porous aramid lithium battery separator material according to claim 4, characterized in that, In the step (3), the volume ratio of NMP to H₂O is 30 - 70: 30 - 70, and the phase transition time is 6 - 12 h.
10. The preparation method of the high-temperature resistant porous aramid lithium battery separator material according to claim 4, characterized in that, In the step (4), the aramid / polypropylene separator after phase transition is dried in a vacuum drying oven. The vacuum drying temperature is 60 - 80 °C, the drying time is 6 - 12 h, and the vacuum degree is 0.09 MPa.